ANALISIS PENERAPAN SISTEM DAN PROSEDUR AKUNTANSI DALAM PENGELOLAAN DANA DESA (Studi Kasus Desa Patengteng Kecamatan Modung Kabupaten Bangkalan) - Masrurotul Jannah Ferdiana; Nur Diana; Afifudin Afifudin (e_Jurnal Ilmiah Riset Akuntansi, 2022)
The purpose of this study was to determine and analyze the application of accounting systems and procedures in managing village funds. The case study in this research is Patengteng Village, Modung District, Bangkalan Regency. This research is primary data research, data collection method using interview and communication technique. This research is a research with a qualitative approach, this study uses the Snobol sampling method and the sample used in this study is 7 Hamlets. The results of this study are 1) At the planning stage, Patengteng village in Modung District, Bangkalan Regency has implemented the planning as stated in Permendagri No. 113 of 2014. At the village fund planning stage, the village government invites the Patengteng village community in development planning. 2)At the stage of implementing the development of the Patengteng village in Modung District, the government as much as possible carries out village development in accordance with the planning and makes openness to the community.3) Then at the administrative stage there is a discrepancy with Permendagri No. 113 of 2014. In Permendagri the village treasurer is required to record cash receipts and disbursements himself, but the treasurer in Patengteng village does not record all cash receipts and disbursements recorded in the receipt but is assisted by the secretary in the recording process so there may be an element of suspicion.4) At the reporting stage it is not in accordance with Permendagri No. 113 of 2014. In Permendagri, the village treasurer should record cash receipts and disbursements himself, but the treasurer in Patengteng village in the recording process is assisted by the Secretary, so there is a suspicion that there is fraud in the recording, so training is needed for the treasurer. 5)The last stage of accountability in Patengteng Village is not in accordance with what is stated in Permendagri No. 113 of 2014. that in the village fund accountability report in Patengteng village there is no information to the community every three months it should be.Keywords: System Implementation, Accounting Procedures, Village Fund Management.